1985
DOI: 10.1104/pp.78.4.803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light Intensity and Oxidized Nitrogen Sources on Hydrogen Production by Chlamydomonas reinhardii

Abstract: Chlamydomonas reinhardii cells, after a period of dark anaerobic adaptation, evolve H2 not only in the dark but also in the light. Our results show that high irradiances impair prolonged H2 evolution, while under low irradiances or darkness H2 evolution proceeds for more than 50 hours. NO3-and NO2-suppress H2 evolution both in the dark or under low irradiance. Apparently the cells prefer these oxidized nitrogen sources to protons as electron acceptors, since both N03-and NOTbecome reduced to NHW+, which is exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…The competition with nitrate for hydrogen production has been previously reported for Synechocystis sp. strain PCC 6803 (24) and in the green alga Chlamydomonas reinhartii (5). We expect that older cultures grown in batch mode will have naturally depleted nitrate from cellular uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The competition with nitrate for hydrogen production has been previously reported for Synechocystis sp. strain PCC 6803 (24) and in the green alga Chlamydomonas reinhartii (5). We expect that older cultures grown in batch mode will have naturally depleted nitrate from cellular uptake.…”
Section: Discussionmentioning
confidence: 99%
“…It might be proposed that the glyoxylate cycle was employed to convert amino acids to fermentable substrates also after the onset of anaerobiosis. The cycle is active in anaerobic C. reinhardtii cells (Gibbs et al, 1986;Willeford and Gibbs, 1989) and dark-anoxic algae excrete ammonium (Aparicio et al, 1985). The products of amino acid degradation might be used for gluconeogenesis, whose induction was indicated by increased amounts of the pyruvate:phosphate dikinase transcript PPD1 and MME2, a transcript encoding an NADP-dependent malic enzyme.…”
Section: Amino Acids and Fas Might Contribute To Energy Generation Inmentioning
confidence: 99%
“…According to Philipps et al (2012), the H 2 production rates are also lower than those obtained under S deficiency. Intriguingly, Aparicio et al (1985) reported no advantage in H 2 production when comparing N-depleted vs ammonium-containing cultures. Hence, H 2 production under N deficiency in Chlamydomonas needs to be better studied.…”
Section: Nitrogen Deficiencymentioning
confidence: 89%
“…Thus, it is proposed that fermentative H 2 production plays an important role in N-depleted cells. As suggested by Aparicio et al (1985), protein degradation could be the major source or reductive equivalents under N deficiency; this suggestion is based on the observation that cells excrete ammonium during H 2 production even in N-depleted cultures. Hence, the pyruvate resulting from protein degradation could contribute to H 2 production via PFR in N-depleted cultures.…”
Section: Nitrogen Deficiencymentioning
confidence: 96%
See 1 more Smart Citation